Material stream network modeling, retrofit and optimization for raw natural gas refining systems. (20th January 2017) - Zhang, Bing J.; Xu, Tao; He, Chang; Chen, Qing L.; Luo, Xiang L.
Abstract: The demand for natural gas is increasing in the energy market because of its lower emissions and sustainable development. This increasing demand for natural gas promotes the capacity expansion of raw natural gas refining systems (RNGRSs), resulting in parallel refining processes in a RNGRS. Optimizing the material stream network between these refining processes is very challenging because of the complex thermodynamics, unit operations and utility configurations. An optimization framework is presented for the retrofit of the material stream network between these refining processes to improve the economic performance. The retrofit framework integrates raw natural gas supply, refining processes, utility subsystems and product delivery and is formulated as a mixed-integer nonlinear programming (MINLP) optimization model to obtain an optimal material stream network to increase profit. The model presented here is applied to a Chinese industrial RNGRS and results in an optimal retrofit. A comparison before and after the retrofit demonstrates a significant increase in profit. Highlights: Material stream networks of RNGRSs are proposed. The MINLP optimization model is presented for the retrofit of RNGRSs. Processes, utility subsystems, crude supply and product delivery are integrated. The retrofit strategy is presented for RNGRSs. An increase of 9.4% in profit is obtained after the optimization retrofit.